HUBUNGAN CYBERBULLYING DENGAN STRES DAN KUALITAS TIDUR SAAT PANDEMI COVID-19 PADA REMAJA DI SMA N 12 KOTA BEKASI - Tiyas Putri Widjayanti (2021)
The pandemic period makes teenagers more often access the internet as a place to interact with peers and learn, but the internet has a negative impact if used by irresponsible people so that it can lead to cyberbullying. Teenagers who are victims and perpetrators of cyberbullying have an impact on stress and sleep quality. This study aims to determine the relationship of cyberbullying with stress and sleep quality during the COVID-19 pandemic in adolescents. This study uses a descriptive-analytical research method with a cross-sectional approach and is analyzed using the Spearman correlation test. The population in this study were teenage victims or perpetrators of cyberbullying at SMAN 12 Bekasi with a sample of 176 students who were taken using a simple random sampling technique. The instruments used were the Cyberbullying and Online Aggression Survey Instrument used for cyberbullying behavior, the Perceived Stress Scale (PSS-10) instrument was used for perceived stress, and the Pittsburgh Sleep Quality Index (PSQI) instrument was used for sleep quality. The results of the study found that there was a relationship between cyberbullying and stress and sleep quality during the COVID-19 pandemic in adolescents at SMAN 12 Bekasi (p = 0.004). The implication of this study is to determine the relationship between cyberbullying and stress and sleep quality as a promotive effort to the impact of cyberbullying on the mental health of adolescents who experience decreased sleep quality and feel stressed. Research advice, teenagers must be careful and wise in using social media and avoid cyberbullying behavior that can have an impact on adolescent mental health.